2013
DOI: 10.1007/s00210-013-0893-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of glycogen synthase kinase 3 (GSK3) inhibition by lithium or selective inhibitors in the central nervous system

Abstract: Glycogen synthase kinase (GSK3) is a constitutively active serine-threonine kinase associated to neurological and psychiatric disorders. GSK3 inhibition is considered a mediator of the efficacy of the mood-stabiliser lithium. This study aimed at comparing the central nervous system effect of lithium with the selective GSK3 inhibitors AZ1080 and compound A in biochemical, cellular, and behavioural tests. Collapsin response mediator protein 2 is a neuron-specific GSK3 substrate. Lithium, AZ1080, and compound A i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Now that their involvement has been demonstrated and is supported by data from animal models, and genetic linkage scanning, we expect more studies will focus on their role in the pathophysiology of these diseases. In a parallel effort, evidence from pharmacological studies shows that CRMP activities are modulated by various psychotropic drugs 75,[86][87]90 and suggests that they are compelling intracytoplasmic targets. Drug discovery technologies targeting the 'CRMP-activity/disease-change' equation are currently explored for neurological diseases, 99,125,126 and may bring new therapeutic interventions for psychiatric diseases as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Now that their involvement has been demonstrated and is supported by data from animal models, and genetic linkage scanning, we expect more studies will focus on their role in the pathophysiology of these diseases. In a parallel effort, evidence from pharmacological studies shows that CRMP activities are modulated by various psychotropic drugs 75,[86][87]90 and suggests that they are compelling intracytoplasmic targets. Drug discovery technologies targeting the 'CRMP-activity/disease-change' equation are currently explored for neurological diseases, 99,125,126 and may bring new therapeutic interventions for psychiatric diseases as well.…”
Section: Discussionmentioning
confidence: 99%
“…29 The mood stabilizer lithium is a potent GSK-3β inhibitor that inhibits CRMP2 phosphorylation in cultured rat cortical neurons. 90 Lithium neurite elongation and branching activities may result in part from changes in CRMP2 phosphorylation. In bipolar patients, lithium treatment increases total grey matter and hippocampal volumes and improves white matter integrity altered by the disease, [91][92][93] suggesting structural changes of neurites.…”
Section: Human Nervous System Diseases: Insights From Crmp-altered Lementioning
confidence: 99%
“…PKC also has been associated with BD pathophysiology and treatment, mainly by regulating pre-and postsynaptic aspects of neurotransmission, modulating the neuronal excitability, neurotransmitter release, and long-term alterations in genic expression and plasticity [57]. Clinical and preclinical studies have demonstrated that the specific GSK-3 or PKC inhibition are able to reverse the manic episodes in bipolar patients [58,59] and the manic-like behavior induced by stimulants in experimental animal models [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, selective inhibition of GSK3␤ reinforces the activity of MAPs, favors microtubule assembly in neurons, and potently promotes neurite growth and sprouting (27,28). Consistently, lithium, an inhibitor of GSK3␤ and Food and Drug Administration-approved mood stabilizer, has been well known to have a potent promotional effect on neural repair in both neurodegenerative diseases and acute neuronal injuries (28,29). More recently, a plethora of evidence suggests that GSK3␤ plays a pivotal role in kidney injury, repair, and regeneration (30 -32).…”
mentioning
confidence: 96%